Threats and potential risks for the functioning of small and medium-sized businesses in Ukraine during the war - Pavlov, Kostiantyn (My University, 2025)
In conditions of war, Ukrainian small and medium-sized businesses have beenunder significant pressure due to numerous economic, social, and political challenges.The direct consequences of the war, including infrastructure destruction, decreaseddemand, rising costs, instability in the financial system, and political uncertainty, create amultifaceted problem for entrepreneurs. A review of the literature revealed that there isno comprehensive study that fully describes the potential risks for the operation of smalland medium-sized businesses in Ukraine during wartime. Therefore, the aim of the studyis to identify the business environment, its threats, and the main areas of activity toensure the functioning and support of small and medium-sized businesses in the wartimeeconomy.The article examines the potential for growth in small and medium-sized enterprises undermartial law. The author presents the essence of the concepts of the topic under study and thepractical impact of these economic units on the economic situation. Medium-sized enterprisesin our country are domestic and multidisciplinary, unlike foreign ones. The author outlines thecommon problems and risks faced by our private business. Among the main driving forces ofthe 'new order' was the reduction of opportunities and harassment in this sector. Under theprevious method of regulation, the state tried not to interfere in the affairs of privatebusinesspeople. The existing tax system is no longer suitable. There are fewer opportunitiesto pay the required and prescribed contributions. This inextricably affects the activities of thestate regulatory apparatus and the provision of the funds necessary for its functioning. Whatis important for the population is the conduct of social policy at the appropriate or previouslevel. The general trends in this important sector of the economy, possible difficulties forcompanies, people working there, and the economy in the updated environment areinvestigated. The formation and development of Ukrainian medium-sized enterprises is a prerequisite for solving socio-economic problems. Most of the unemployed are involved inentrepreneurial activities, adjusting credit and tax policies to stimulate the production,formation, and development of Ukrainian medium-sized enterprises and the transition toinnovative economic development. The author outlines the state apparatus's actions intaxation, organization, assistance, and innovation-especially changes in the energy andagricultural sectors, as Ukraine specializes in the latter. The geopolitical situation, in general,is also important. Therefore, finding out the situation and investigating the risks is important.This is a unique situation that requires our attention, and it is the reconstruction that needs tobe done. After the victory, a new Ukraine must emerge, worthy of the heroic people whoinhabit it.
У період війни український малий та середній бізнес опинився під вели-ким тиском через численні економічні, соціальні та політичні виклики. Безпосереднінаслідки повномасштабного вторгнення, зокрема, руйнування інфраструктури, ско-рочення попиту, зростання витрат, нестабільність фінансової системи, а такожневизначеність у політичному середовищі, створюють багатогранну проблему дляпідприємців. Аналіз джерел літератури показав, що не представлено ґрунтовногодослідження, яке б дозволило в повні мірі описати потенційні ризики для роботималого та середнього бізнесу в Україні в умовах війни. Отже метою дослідження євизначення середовища господарювання, його загроз та основних напрямівдіяльності для забезпечення функціонування та підтримки малого та середньогобізнесу в умовах економіки воєнного стану.Проаналізовано стан малого та середнього бізнесу, що функціонує в умовахвоєнного часу. Розкрито сутність ключових понять теми та проаналізовано впливцих економічних суб’єктів на загальну економічну ситуацію. Відповідно до визначеньмалі та середні підприємства України характеризуються вітчизняним ібагатопрофільним спрямуванням, що відрізняє їх від іноземних аналогів. Визначеноосновні проблеми та ризики, з якими зіткнувся приватний бізнес. Серед ключовихфакторів, що ускладнюють діяльність цього сектора, є скорочення можливостей тапосилення обмежень. У минулому держава дотримувалася політики невтручання усправи приватного бізнесу. Однак чинна податкова система більше не відповідаєсучасним викликам, оскільки спроможність підприємств сплачувати встановленівнески суттєво знизилася. Це, у свою чергу, впливає на ефективність державногорегулювання та наповнення бюджетних фондів, необхідних для соціальних про-грам. Окреслено загальні тенденції розвитку цього важливого сектора економіки,виклики для підприємств і працівників, а також специфіку ведення бізнесу в оновле-них умовах. Розвиток малих і середніх підприємств в Україні є ключовим факторому вирішенні соціально-економічних проблем. Значна частина безробітного населен-ня знаходить зайнятість у сфері підприємництва, що підкреслює важливість коригу-вання кредитної та податкової політики. Це сприятиме стимулюванню виробництва,зростанню бізнесу та переходу економіки на інноваційну модель розвитку. Держававже вжила заходів для підтримки бізнесу, зокрема в частині оподаткування,організації, сприяння інноваціям та розвитку стратегічних галузей, таких як енерге-тика й сільське господарство, що є ключовими для України. Окрему увагу вдослідженні приділено геополітичному контексту, який суттєво впливає на економікукраїни в цілому. Особливі обставини вимагають комплексного підходу до оцінкиризиків і визначення шляхів відновлення економічної діяльності. Відбудова країнипісля повномасштабного вторгнення має стати основою для створення новоїУкраїни, яка відповідатиме прагненням та героїзму її народу.
Keywords: economy; enterprises; economic sector; medium-sized business; entrepreneurship; state apparatus; eopolitical situationg; risks; small business; D81; P34; O17; L26; H56; 338.24:338.22